Time-dependence of the transmission matrix of a specialty few-mode fiber - YAMMINE, Jean; TANDJE, S. H. Arsène; DOSSOU, MICHEL; BIGOT, Laurent; ANDRESEN, Esben (My University, 2018)
We report a time-resolved measurement of the full transmission matrix (TM) of a short length of specialty annular-core few-mode ber which guides 10 vector modes. We show how our method can isolate the ber TM from "misalignment" contributions from optics upstream and downstream of the ber. From measurements spanning two days we extract the drift of the ber TM. We show that drifts in the TM elements are mostly described as correlated phase variations rather than amplitude variations. We show that an empirical model of the ber TM parametrized in one parameter can successfully account for the drift.
Keywords: Ring-core ber; OAM mode; Vector mode; Multi-modal channel; Modal division multiplexing; Space-division multiplexing; Fiber optic communications